Green Synthesis of Bioactive CuO@Fe3 O4 @Walnut Shell Nanocomposite Using Crataegus azarolus Var. aronia L. Extract and its Antivasoconstrictive Action on Rat’s Aortic Smooth Muscle - Sarbast A. Mahmud (Polytechnic Journal)
The antioxidant potential of Crataegus azarolus Var. aronia aqueous extract was used as reducing and stabilizing media to the green synthesis of bioactive CuO@Fe3O4@Walnut shell nanocomposite (NCs). The ability of the plant extract as bioreducing medium was proved using Fourier-transform infrared spectroscopy and ultraviolet–visible spectroscopy. While, the structural identification of synthesized CuO@Fe3O4@Walnut shell NCs was proved using the scanning electron microscopy, electron dispersive spectroscopy, elemental mapping, and point analysis. Then, the antivasoconstriction effects of CuO@ Fe3O4@Walnut shell NCs (5*10−2 mg/ ml) and (1*10−1 mg/ ml) on rats isolated thoracic aortic smooth muscle cells were studied. Green synthesized CuO@Fe3O4@Walnut shell NCs showed effective antivasoconstriction activity against norepinephrine (NE) (1*10−9–10−4 M) induced contraction in endothelium-intact and endothelium-denuded rats aortic smooth muscle. In conclusion, the aqueous extract of C. aronia acts as potential reducing and stabilizing media to the green synthesis of bioactive CuO@Fe3O4@Walnut shell NCs and the NCs play an important role against contractile effects of NE on rats’ aortic smooth muscle.